Medicinal uses and Pharmacological activity of Mothirakanni (Hugonia mystax Linn). - A Review - Sounthararajan, K.; Vidya Dharshini, K.; Sivaranjini, S. (Siddha Papers 2015, 2015)
Hugonia mystax Linn. belonging to family Linaceae, commonly known as Mothirakanni. It is a rambling leafy tomentose climbing shrub found in low country, especially in dry regions of Sri Lanka and throughout the world, with a multitude of uses in traditional medicine. Review of literature revealed less work on this plant; hence the Sri Lankan traditional practitioners are using this plant to treat the poisonous bites. Mothirakanni is effectiveness in treating to reduce inflammatory tumours, snake bite, fever and worm infestation. Hugonia mystax is an anthelmintic, febrifuge and Antidote. In this paper general medicinal uses, Pharmacological activities and phytochemistry of the plants have been revived.
Keywords: Mothirakanni; Hugonia mystax Linn; Medicinal uses; Pharmacological activity